Obsessive–compulsive symptoms in at‐risk mental states for psychosis: associations with clinical impairment and cognitive function. (26th February 2014) - Zink, M.; Schirmbeck, F.; Rausch, F.; Eifler, S.; Elkin, H.; Solojenkina, X.; Englisch, S.; Wagner, M.; Maier, W.; Lautenschlager, M.; Heinz, A.; Gudlowski, Y.; et al.
<x xml:space="preserve">Abstract</x> Objective Obsessive–compulsive symptoms (OCS) constitute a major comorbidity in schizophrenia. Prevalence estimations of OCS for patients with at‐risk mental states (ARMS) for psychosis vary largely. It is unclear how ARMS patients with or without comorbid OCS differ regarding general psychosocial functioning, psychotic and affective symptoms and neurocognitive abilities. Method At‐risk mental states patients (n = 233) from the interventional trial PREVENT (Secondary Prevention of Schizophrenia) were stratified according to the presence or absence of comorbid OCS and compared on several clinical variables. Results Patients, who fulfilled the criteria for obsessive–compulsive disorder (OCD) or presented with subclinical OCS (ARMSposOCS sample), did not significantly differ from patients without OCS (ARMSnegOCS) with regard to gender, age, premorbid verbal intelligence and levels of education. Furthermore, similar severity of depressive syndromes, basic cognitive, attenuated psychotic and brief limited intermittent psychotic symptoms were found. However, ARMSposOCS patients showed more impairment of psychosocial functioning and higher general psychopathology. In contrast, they scored higher in cognitive tasks measuring working memory and immediate verbal memory. Conclusion Findings extend upon previous results due to the multidimensional assessment. Subsequent longitudinal studies might elucidate how comorbid OCS influence differential treatment response, especially to cognitive behavioural interventions and the transition rates to psychosis.